2006
DOI: 10.1111/j.1574-6968.2006.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of clinical isolates ofStreptococcus pneumoniaewith human complement factor H

Abstract: PspC recruits complement factor H (FH) to the pneumococcal surface. While there is differential expression of pspC during infection, detection of PspC on the surface of viable pneumococci is difficult due to variability among PspCs. We analyzed FH binding to detect PspC expression on the surface of pneumococcal isolates from different pathological sources. Using flow cytometry, we investigated FH-binding to 89 low-passage clinical isolates classified by disease manifestation (systemic, mucosal, or carriage). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…The improved survival of pneumococci expressing PspC or Hic in a systemic mouse infection model and in microglial cells provides further evidence for the importance and versatility of PspC in different host niches (29,31). A recent study indicated that carriage isolates, which produce lesser amounts of CPS than the invasive isolates, recruit significantly more factor H than the systemic isolates (53). Similarly, our binding experiments indicate that the CPS interferes with the recruitment of factor H.…”
Section: Discussionsupporting
confidence: 47%
“…The improved survival of pneumococci expressing PspC or Hic in a systemic mouse infection model and in microglial cells provides further evidence for the importance and versatility of PspC in different host niches (29,31). A recent study indicated that carriage isolates, which produce lesser amounts of CPS than the invasive isolates, recruit significantly more factor H than the systemic isolates (53). Similarly, our binding experiments indicate that the CPS interferes with the recruitment of factor H.…”
Section: Discussionsupporting
confidence: 47%
“…For the remaining strain, an ST6A strain, there was a low level of FH binding in serum to the ⌬pspC strain compared to bacteria incubated on PBS although the biological significance of this is uncertain. As has been recently demonstrated for a large number of clinical isolates (36), the degree of FH binding (represented by a fluorescence index) (9,49) varied significantly between the strains (Fig. 1D).…”
Section: Resultsmentioning
confidence: 59%
“…Furthermore, allelic variation of PspC will affect the avidity of antibody to each allelic variant and means that different sets of primers for real-time PCR will be necessary, complicating accurate investigation of PspC expression. Allelic variations in PspC structure (17,36) may also affect FH binding and could be investigated by exchanging pspC alleles between strains. The effects of loss of PspC on C3b/iC3b deposition were strikingly varied, with a massive increase in C3b/iC3b deposition on the ST6A ⌬pspC strain, large increases on the ST4 and ST6B ⌬pspC strains, only a small increase on the D39 ST2 ⌬pspC strain, no consistent effect on the ST17 and ST23F FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative pathway can amplify the amount of C3 initially deposited on the organism. The alternative pathway is inhibited by factor H, and previous studies have shown that pneumococci can bind to factor H (28,(36)(37)(38). Both carriage and invasive strains bound similar amounts of the alternative pathway inhibitor factor H (data not shown), thus making it unlikely that differences in regulation of the alternative pathway positive feedback loop accounted for differences in C3 binding.…”
Section: Discussionmentioning
confidence: 90%